Digital Art Masters : Volume 4 - 3dtotal.Com, 3dtotal; 3DTotal.com (Firm); Safari, an O'Reilly Media Company (Routledge, 2012)
Meet some of the finest 2D and 3D artists working in the industry today and discover how they create some of the most innovative digital art in the world. More than a gallery book or a coffee table book- Digital Art Masters Volume 4 includes over 50 artists and 900 unique and stunning 2D and 3D digital art. Beyond the breaktaking images is a breakdown of the techniques, challenges and tricks the artists employed while creating stunning imagery. This volume, much like the previous volumes is not your standard coffee table book nor is it our usual how-to-book. This book offers inspiration and insight for the advanced amateur and professional CG artists. The Digital Art Masters series has expanded upon the competition's gallery book concept and has added the insight and experiences of professional CG artists worldwide. Divided into 5 sections, Sci-Fi, Scene, Fantasy, Character and Cartoon, Each featured artist segement will include the thought processes behind creating unique digital images and an artist portfolio for further inspiration. Find your inspiration and discover the tips, tricks and techniques that really work.
Keywords: Computer art